Peran Serta Masyarakat Dalam Proses Penyusunan Analisis Mengenai Dampak Lingkungan Hidup - Ciptaningrum, Yurike Inna Rohmawati; Atikah, Warah; Fadhilah, Nurul Laili (Lentera Hukum, 2017)
Environmental Impact Analysis or called EIA is a preventive measure to prevent environmental damage as well as a prerequisite for getting an environmental license. The EIA in its preparation should involve the society, but there are still many societies that have not been fully involved by investors/business actors and the government. Whereas the society has the right and obligation to keep environment. The lack of social involvement to result in further about an assessment of social participation in the process of preparing EIA. The written uses normative juridical methods in addressing issues related to guarantees of protection concerning society involvement in the process of preparing to EIA and the legal consequences of non-involvement of the society. Discussion results show that society involvement in the EIA compilation process has been protected and guaranteed its rights by regulation but the implications of the regulation are still minimal. Consequently, the involvement of the public with the implications of EIA documents may be submitted to the Administrative Court and investors/business actors shall be required to improve the phase of the non-involvement of the society in the process of preparing the EIA in accordance with the court's verdict. Keywords: Social Participation, Environmental Impact Analysis, Administrative Court